2017
DOI: 10.3389/fphys.2017.00988
|View full text |Cite
|
Sign up to set email alerts
|

Stemodia maritima L. Extract Decreases Inflammation, Oxidative Stress, and Alveolar Bone Loss in an Experimental Periodontitis Rat Model

Abstract: Periodontitis is very prevalent worldwide and is one of the major causes of tooth loss in adults. About 80% of the worldwide population use medicinal plants for their health care. Stemodia maritima L. (S. maritima) antioxidant and antimicrobial effects in vitro as well as anti-inflammatory properties. Herein, the potential therapeutic effect of S. maritima was assessed in rats subjected to experimental periodontitis (EP). EP was induced in female Wistar rats by nylon thread ligature around 2nd upper left molar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 50 publications
(74 reference statements)
1
15
0
1
Order By: Relevance
“…floribundum increased both markers for oxidative stress. These data are in accordance with previous results of our group showing the antioxidant effect of natural extracts from Stemodia maritima L. and Calendula offinalis [24], [31]…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…floribundum increased both markers for oxidative stress. These data are in accordance with previous results of our group showing the antioxidant effect of natural extracts from Stemodia maritima L. and Calendula offinalis [24], [31]…”
Section: Discussionsupporting
confidence: 93%
“…Also, some authors have suggested the potential involvement of both pro- and anti-inflammatory cytokines in the regulation of the chronic inflammatory periodontitis. In fact, our research group recently showed that ligature-induced periodontitis in rats was related to a significant decrease in gingival levels of IL-10, an anti-inflammatory cytokine [24] In the preset study, P . floribundum (10mg/kg) decreased TNF-α, IL1-β, and IL-8/CINC-1 gingival levels and transcription of TNF-α, IL1-β, RANK and RANKL genes, while elevated IL-10 gingival levels, which suggestes that the protective effect of P .…”
Section: Discussionmentioning
confidence: 99%
“…Albino rats were chosen for this study because they are considered relevant models for experimental periodontal research (Struillou et al, 2010), owing to the similarity in the structure of their dentogingival area and nature of the junctional epithelial attachment (Yamasaki et al 1979). The structure and organization of rat periodontal tissue and 1335 anatomy in the molar region is also similar to that of humans, with the exception of their sulcular epithelium, which is keratinized rather than non-keratinized as in humans (Teixeira et al, 2017).…”
Section: Discussion:-mentioning
confidence: 69%
“…SOD was valued as the absorbance at 560 nm. 25 For CAT detection, 20 µl homogenate was mixed with 5 nM Tris-HCl EDTA buffer and 3% H 2 O 2 . The absorbance at 230 nm was detected immediately and 6 mins after mixing samples.…”
Section: Methodsmentioning
confidence: 99%